Court of Justice of the European Union and Ukrainian Legal Order: Some Pre-accession Considerations - Haletska, Nataliya; Savchuk, Anastasiia (Review of European and Comparative Law, 2023)
As the European Union candidate country (hereinafter the EU), Ukraine is one step away from becoming an EU Member State. From this point on, the country will be subject to the influence of EU institutions, including the Court of Justice of the European Union (hereinafter the CJEU). It is suggested that upon the accession of Ukraine, the CJEU’s impact will be comparable to the influence on legal orders of other EU Members States provided necessary preparatory steps, such as training for judges, are taken. It is established that the main functions of the CJEU are to interpret and ensure the uniform application of EU law in each EU Member State, to ensure compliance with EU law by EU countries and institutions, to ensure respect for the rights and freedoms of individuals, to provide clarifications to national courts, and to promote “positive integration” and “negative integration” of EU Member States. With respect to the above-mentioned functions, it is argued that the CJEU will become an effective tool for Ukraine after it accedes to the EU. It will facilitate the harmonization of national legislation with EU standards through the application of precedents by national courts, influence the activities of legislative bodies, and help prevent future complaints by becoming an additional “quasi-supervisory” body in Ukraine. It will also provide interpretation of the EU law at the request of national courts through the preliminary rulings and procedures, protecting human rights and freedoms by enabling individuals to apply to the CJEU for protection. At the same time, arguably, Ukraine will also impact the functioning of the CJEU by increasing the caseload and appointing judges from Ukraine as well as potentially Advocate-General. Given these potential implications, certain preparatory actions, like preparing a cadre reserve, may be considered at the present moment. Finally, the authors argue that even before Ukraine’s accession, the CJEU has an indirect impact on the Ukrainian legal order. It is suggested that constitutional amendments, as well as certain institutional changes like the establishment of an impartial judicial system and empowering a Ukrainian state body with powers to execute CJEU decisions, will need to take place prior to the accession, which is a demonstration of the CJEU’s indirect influence.